THE PROBLEMS OF INFORMATION SUPPORT OF GEOPHYSICAL TOMOGRAPHY INTERPRETIVE TECHNOLOGIES - Vyzhva, S.; Prodayvoda, G.; Virshilo, I.; Kozionova, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
New interpretation technology of geophysical tomography is considered in the paper. Technology based on 3-dimensional nonlinear dynamic and anisotropic model. Theoretical and methodological developing principles are shown for a number of geophysical applications.